Forecasting of Tomato Price in Karnataka using BATS Model - Vinay H.T.; Pradip Basak; Arunava Ghosh; Sankalpa Ojha; Chowa Ram Sahu (Journal of the Indian Society of Agricultural Statistics, 2025)
Tomato plays a vital role in Karnataka’s agro-processing and food industries, contributing significantly to the state’s economy. Even though tomato production in Karnataka is substantial, the state’s market is characterized by price volatility. Tomato prices can undergo drastic fluctuations within short time periods, posing severe challenges to the farmers and consumers. To address these problems, time series models, such as Exponential Smoothing, ARIMA, SARIMA, BATS and TBATS have been implemented to forecast the tomato prices in Kolar market of Karnataka state using monthly wholesale prices data from the year 2010 to 2022. Among the applied models, BATS showed superior performance in terms of model validation criteria such as Root Mean Square Error and Mean Absolute Percentage Error.